M2‐like macrophage‐derived exosomes facilitate metastasis in non‐small‐cell lung cancer by delivering integrin αVβ3. Issue 1 (23rd December 2022) - Huang, Lamei; Wang, Fang; Wang, Xueping; Su, Chaoyue; Wu, Shaocong; Yang, Chuan; Luo, Min; Zhang, Jianye; Fu, Liwu
Abstract: Metastasis is the most prevalent cause of cancer deaths, and immunological components of the tumor microenvironment, especially tumor‐associated macrophages (TAMs), play a vital role in cancer metastasis. However, the underlying mechanisms of TAMs on non‐small‐cell lung cancer (NSCLC) metastasis remain largely unexplored. Herein, we demonstrated that M2‐like TAMs facilitate the migration and invasion of cancer cells in vitro and in vivo through intercellular delivery of M2‐like macrophage‐derived exosomes (M2‐exos). Importantly, we found that M2‐exos had considerably higher levels of integrin (ITG) αV and β3. The impact of M2‐like macrophage‐mediated invasion and migration of NSCLC cells was clearly decreased when ITG αVβ3 was blocked. Mechanistically, exosomal ITG αVβ3 produced from M2‐like macrophages successfully triggered the focal adhesion kinase signaling pathway in recipient cells, boosting the migratory and invasive abilities of NSCLC cells. Clinically, we found that metastatic NSCLC patients had greater ITG αV and β3 expression, which was associated with a worse prognosis. This study reveals a novel mechanism by which M2‐exos significantly increased NSCLC cell migration and invasion by delivering integrin αVβ3. Exosomal ITG αVβ3 can be used as a potential prognostic marker, and blocking ITG αVβ3 could be a viable treatment option for preventing tumor metastasis. Abstract : Tumor‐associated macrophage‐derived exosomes were significantly rich in integrin (ITG) αV and β3. Exosomes derived from tumor‐associated macrophages are taken up by tumor cells and activate the FAK signaling pathway to enhance the migration and invasion ability of tumor cells.